The union structure, goals and policies for collective bargaining - Leap, Terry 1948- (1995)
This chapter also investigates unions as democratic institutions, and unions relation to organized crime. This chapter concludes by describing typical union goals in collective bargaining.
Introduction -- The major levels of unionism -- the AFL-CIO -- The International unions -- The local unions -- Merger activities and organized labor -- Unions democratic institutions -- Labor unions and organized crime -- Union goals in collective bargaining -- Summary and conclusions.
Photocopy.
Source: Leap, Terry. Collective Bargaining and Labor Relations: Chapter 6. 2nd ed. Englewood Cliffs, N.J. : Prentice-Hall, c1995.
Includes bibliographical references (p. 218-223)
Keywords: Collective bargaining; Industrial relations